STRENGTHENING ECONOMICS LESSON PLANNING THROUGH LOCAL WISDOM INTEGRATION AND INTERACTIVE MEDIA FOR SENIOR HIGH SCHOOL STUDENTS - Helena Rosalia Parera; Maria Elisabeth Balu Vengi; Maria Klaret Ngina (LPPM Universitas Flores, 2026)
This community service program aimed to strengthen the competence of economics teachers and to improve student engagement in learning through training in lesson planning based on local wisdom and the use of interactive learning media at SMAK Syuradikara. The program adopted a participatory approach through needs analysis, workshop activities, guided practice, classroom implementation, and evaluation. The participants were economics teachers and selected students involved in trial implementation. The activities focused on the development of contextual lesson plans by integrating local economic practices, social values, and community-based examples into learning materials. The workshop also introduced simple interactive media such as digital modules, interactive presentations, and smartbook-style materials that could be used offline or online according to school conditions. The evaluation showed an improvement in teachers’ understanding of lesson planning, better quality of lesson plans, and higher student participation during trial lessons. The program produced several local-wisdom-based lesson plans, learning media drafts, and a practical guide for teachers. The results indicate that contextual and interactive learning design can strengthen the relevance, attractiveness, and effectiveness of economics learning in senior high school.